Bacteremia hospitalar por bacilos Gram-negativos multiresistentes: fatores de risco e detecção de ESBL, AmpC e metalo-β-lactamase - Dantas, Raquel Cristina Cavalcanti (2011)
The higher incidence of bacteraemia due to multiresistant microorganisms in recent years, coupled with the emergence and spread of β-lactamases, have become a great public health problem, since in patients infected with these strains is more likely to receive inadequate antimicrobial therapy, directly reflected in mortality rates. We conducted a case-control study in order to identify risk factors associated with bacteraemia due to MDR-GNB isolates and a cohort study to determine the prognostic factors associated with mortality among patients with bloodstream infection diagnosed from May 2009 through February 2010. The production of extended-expectrum β-lactamase (ESBL) and AmpC was determined in isolates of Enterobacteriaceae and metallo-β-lactamase (MBL) among Pseudomonas aeruginosa was evaluated among isolates of blood and catheter tip culture. The univariate analysis showed that the development of bacteraemia caused by multiresistant gram-negative bacilli was associated with previous surgery, use > 2 invasive procedures, including mechanical ventilation, urinary catheter, tracheotomy and use of antibiotics, especially fluoroquinolones. Previous surgery, tracheostomy and inadequate therapy were independently associated with the multidrug resistance. The rate of ESBL producing isolates was 58% and 32% for K. pneumoniae and E. coli, respectively. Among Enterobacteriaceae, the AmpC enzyme was detected in 8.6% of isolates and the MBL phenotype was detected in 34% of the P. aeruginosa isolates. The most microoorganisms showed high rates of antimicrobial resistance. The resistance was associated with inadequate antimicrobial therapy and higher mortality rates. The risk for death was higher in patients over 60 years old, MDR-GNB bacteraemia, heart disease and inappropriate antimicrobial therapy, but just advanced age was independently associated with death. There was also a high frequency of phenotypes ESBL, AmpC and metallo-β-lactamases among isolates, associated with higher rates of resistance to most antimicrobial agents used in patients.